2016
DOI: 10.1038/nature17150
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-dependent but not sequence-specific piRNA adhesion traps mRNAs to the germ plasm

Abstract: The conserved Piwi family of proteins and piwi-interacting RNAs (piRNAs) play a central role in genomic stability, which is inextricably tied with germ cell formation, by forming ribonucleoproteins (piRNPs) that silence transposable elements (TEs)1. In Drosophila melanogaster and other animals, primordial germ cell (PGC) specification in the developing embryo is driven by maternal mRNAs and proteins that assemble into specialized mRNPs localized in the germ (pole) plasm at the posterior of the oocyte2,3. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
132
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(140 citation statements)
references
References 45 publications
7
132
0
1
Order By: Relevance
“…piRNA-mediated gene regulation has been shown to be crucial in the embryonic development of both fruit flies and mosquitoes (Halbach, 2020, Rouget, Papin et al, 2010, Vourekas, Alexiou et al, 2016. Early embryonic development of animals is driven by maternally provided mRNAs until maternal-to-zygotic transition (MZT), during which the zygotic genome is activated and maternal mRNAs are degraded (Tadros & Lipshitz, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…piRNA-mediated gene regulation has been shown to be crucial in the embryonic development of both fruit flies and mosquitoes (Halbach, 2020, Rouget, Papin et al, 2010, Vourekas, Alexiou et al, 2016. Early embryonic development of animals is driven by maternally provided mRNAs until maternal-to-zygotic transition (MZT), during which the zygotic genome is activated and maternal mRNAs are degraded (Tadros & Lipshitz, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Piwi proteins are known to enlist germline-specific Piwi-interacting RNAs (piRNAs) to suppress transposable elements and protect the integrity of the genome in germ cells (Juliano et al, 2011; Siomi et al, 2011). We and others recently showed that the Piwi/piRNA machinery also functions in regulating protein coding genes in germ cells (Gou et al, 2014; Zhang et al, 2015; Barckmann et al, 2015; Watanabe et al, 2015; Vourekas et al, 2016). Extensive genetic studies in worms, flies, fish, and mice indicate that Piwi proteins are essential for gametogenesis in animals (Cox et al, 1998; Harris and Macdonald, 2001; Deng and Lin, 2002; Kuramochi-Miyagawa et al, 2004; Carmell et al, 2007; Houwing et al, 2008; Batista et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Later in development, most postnatal piRNAs are produced from specific genomic regions termed piRNA clusters and divided into two types, depending on the stage of their expression: prepachytene clusters arising from genic sequences, and pachytene clusters of intergenic origin (Li et al 2013a). The details of both biogenesis and function of these two types of postnatal piRNAs in the developing testis remain unclear; however, several reports have proposed various hypotheses relating pachytene piRNAs to TE silencing or the control of gene expression in either an indiscriminate or targeted manner (Gou et al 2014;Hirano et al 2014;Goh et al 2015;Zhang et al 2015;Vourekas et al 2016).…”
Section: Introductionmentioning
confidence: 99%